Understanding Responses to Bullying From the Parent Perspective - Stives, Kristen L.; May, David C.; Mack, Michayla; Bethel, Cindy L. (Frontiers in Education, 2021)
Relatively little scholarly work addresses parental experiences with bullying in the United States. This lack of understanding about parental perceptions of bullying is a gap in both the scholarly research and the development of effective bullying prevention programming. This paper presents data from responses to a series of open-ended questions about perceptions of and experiences with bullying from 50 parents in a southeastern state. Parents self-reported their level of concern about bullying, their perceptions of why bullying occurs and the extent of bullying at their school, and their communication strategies with their children about bullying. Findings demonstrate that most parents (1) view bullying as problematic and are somewhat fearful of bullying affecting their child, (2) are confident their child is not telling them about all bullying situations they experience, and (3) are more than willing to approach school administrators when their children are victims of bullying. The findings suggest that parents remain concerned about bullying and its problematic nature, and efforts to encourage children to report bullying to adults are not entirely effective. Consequently, bullying prevention training will benefit from greater parental involvement with (and reinforcement of) bullying prevention strategies learned by children at school. Implications for policy and research are also discussed.